Rearranging Agrarian Law Politics in the Land Regulation System in Indonesia - Damianus Krismantoro (Global Writing Academica Researching & Publishing, 2020)
Resetting agrarian law is considered urgent, severe, and effectively managed. This is due to political, and regime changes and is intended so that social welfare and human values ​​can be well constructed. The land has a significant role in the life of all people, such as the role in housing, plantation businesses, agricultural businesses, mining businesses, and others. Land law politics is a government policy in the field aimed at the designation and use of the ruler or land owner, the appointment of land use to ensure legal protection and improve welfare and encourage economic activity through the enactment of the Land Law and its implementing regulations which are the main themes of this research. This research methodology uses normative studies or literature studies because the studies obtained are based on references from books, articles, and regulations related to agricultural law or land policy. The results of the study can be concluded that the agricultural law policy that was formed through the UUPA No. 5 of 1960 concerning the Principles of Agrarian Law, which is already sixty years old, needs to be reformulated to avoid the distortion effect that can have such consequences both on the sociological and philosophical side. One of the reformulation concepts is within the corridor of the concept of regional autonomy.